How important are CSR companies for nations’ growth? - Škare, Marinko; Golja, Tea (Journal of Business Economics and Management, 2013)
The paper provides new empirical evidence on the positive link between corporate social responsibility and income growth. Using available data for 26 countries over 2000–2008 we investigate cross-country growth differences by adding new variable (corporate social responsibility) to the standard growth regression model. We show that corporate social responsibility impact on growth is statistically significant but limited in size. Moreover, the inclusion of corporate social responsibility variable improves the fit of the regression. Countries with higher corporate social responsibility penetration as India achieve higher income growth rates. Evidence of the positive link between corporate social responsibility presented in this study encourage but further research on mechanism how socially responsible behavior affects growth is necessary.